Staatsbürgerschaftsregime im Wandel: oder: Die Gleichberechtigung wird zu Markte getragen Das Beispiel Kanada - Jenson, Jane; Phillips, Susan D (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
The article presents a conceptualisation of 'citizenship regime' created out of a neo-institutionalist approach to political economy and then uses the concept to examine changes in the Canadian citizenship regime over time. The basic proposition is that if the postwar years were marked by regimelike discursive and practical coherence in a wide range of institutional connections between state and citizens, states' and citizens' responses to the economic and political conditions of the late 20th century are dismantling and reconstituting citizenship, so that the postwar regime exists no more.